Pelaksanaan Pembelajaran Seni Budaya Melalui Daring Di SMP Negeri 26 Padang - Muftiya El Khair; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2021)
The purpose of this research is to find out how the implementation of online learning of art and culture in grade VII.3 SMP Negeri 26 Padang. This type of research is using descriptive data that produces qualitative data. The instrument of this research is the researchers themselves. The data was obtained by collecting data conducted by means of literature studies, observations, and interviews as well as documentation containing photographs during the learning process conducted online. Based on the results of the study, that the implementation of online learning of cultural arts with the results of students' learning in grade VII.3 on musical ensemble material is less than maximum. Because in the process of practical learning that should not be achieved in online learning, due to the lack of media owned by learners so that evaluation can only be done with theory only.